Research Landscape of Diabetes mHealth Technologies - Pedro F. Castillo-Valdez; Marisela Rodriguez-Salvador; Yuh-Shan Ho (Foresight and STI Governance)
In recent years, more and more generic technologies have appeared, allowing one to find answers simultaneously along different dimensions, “fan” solutions for urgent and complex problems are synthesized and cumulative effects emerge. This article analyzes the potential of such technologies using the example of mobile health (mHealth), which provides rapid access to medical services even in the most remote regions, mitigating the inequalities between different segments of the population in this regard. The implementation of mobile health becomes especially important in the context of the rapid spread of chronic and autoimmune diseases, which strongly impact the quality and duration of life. Smart applications based on AI and virtual reality provide the opportunity to manage one’s health by combining patient self-monitoring with rapid consultations with medical staff. By doing so, risks are reduced and physiological and mental well-being is enhanced. This article conducts a large-scale literature review of diabetes management techniques through mobile technology to systematize and identify the most advanced solutions. For such innovations to maximize their impact, public health policies must be aligned with a digitalization strategy.